Integración onomástica y social de los indígenas de la Beturia céltica (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In the Celtic Beturia has been found 232 persons and 27 carry indigenous onomastic (18 from the Beturia and 9 inmigrants). The most important characteristics of this group is that they use the roman onomastic structure correctly and the less common support in the region: the stele, that is usually engraved in the regional material. It is also characteristic their finding in the territorium (the natives are almost inexistent in the city). This could suggest that this is a marginal group and with not much integration in the  Roman  society.  However,  these  features  are  also  normal  in the most romanized groups. As the result, the indigenous group behaves in the same way as the rest of the population.
Keywords: Celtic Baeturia; Indigenous; Epigraphic support; Onomastic integration; Social integration